AB0763 Olfactory and respiratory nasal function in churg-strauss syndrome. (23rd January 2014) - Laudien, M.; Petersen, H.; Götz, P.; Bremer, P.; Ambrosch, P.; Gross, W.; Moosig, F.
Abstract : Background: Nasal involvement seems to be common in Churg-Strauss Syndrome (CSS, (1, 2)). Detailed investigations of nasal function are not available. Objectives: To analyze nasal function in CSS regarding especially olfactory and respiratory capacities using validated modern test systems. Methods: From 6/1990 until 12/2009 96 CSS-patients (297 contacts) were included following standardized examination protocols (mean age 54, 47 female, 49 male). All patients had clinical and/or histological evidence for vasculitis and fulfilled the ACR criteria for classification. They were examined using rigid endoscopes (n=96), ENT activity score (ENTAS (3), n=37), anterior rhinomanometry (n=96), sniffin'sticks and acetic acid (n=63). Results: Of 48 contacts investigated using ENTAS 38 showed no and 10 mild to high endonasal activity. By endoscopy in 86 contacts polyps, 65 septal deviations and 24 hyperplasias of the turbinates were detected. In 35 contacts (30 patients, 31%) profoundly nasal obstruction was detected and showed no correlation to ENTAS (p=0.5), polyps (p=0.7), septal deviation (p=0.5) or hyperplasia of the turbinates (p=0.08). Fourteen patients (22%) showed dysosmia. CSS-patients with compared to CSS-patients without olfactory dysfunction showed significantly less polyps (p=0.027), less often hyperplasia of the turbinates (p=0.017), less often subjective obstruction of the nose (0.002), no endonasal activity (ENTAS, p=0.04) and higher frequency of sinusitis (anamnestic data, p=0.035). No significant correlation could be detected ragarding nasal obstruction or trigeminal dysfunction and olfactory function (p=0.8, p=0.48). Compared to the general german population the risk for olfactory dysfunction is significantly increased in CSS patients Odds ratio 5.4 (95% CI 1.8 to 16, p=0.0018). Conclusions: Nasal function in CSS is severely disturbed. 31% of CSS-patients suffer from profoundly nasal obstruction being one of the major complaints in chronic rhinosinusitis leading to reduced quality of life and tremendous medical costs. Olfactory dysfunction in CSS-patients compared to healthy population seems to be an effect of disease rather than obstruction and no general affection of cranial nerves was detectable. Further investigation to analyze olfactory function in detecting odors, differentiating odors and threshold as well as electrophysiological studies to differentiate peripheral and central origin of olfactory dysfunction are currently undertaken. References: Bacciu A, Buzio C, Giordano D, Pasanisi E, Vincenti V, Mercante G, Grasselli C, Bacciu S. Nasal polyposis in Churg-Strauss syndrome. Laryngoscope 118: 325-9, 2008. Bacciu A, Bacciu S, Mercante G, Ingegnoli F, Grasselli C, Vaglio A, Pasanisi E, Vincenti V, Garini G, Ronda N, Ferri T, Corradi D, Buzio C. Ear, nose and throat manifestations of Churg-Strauss syndrome. Acta Otolaryngol 126: 503-9, 2006. Garske U, Haack A, Berltran O, Flores-Su'rez LF, Bremer JP, Lamprecht P, Hedderich J, Quetz J, Gross WL, Ambrosch P, Laudien M. Intra- and Interrater reliability of endonasal activity estimation in Granulomatosis with Polyangiitis (Wegener's). Clinical and Experimental Rheumatology accepted.2012. Disclosure of Interest: None Declared